The Binding Authority of the Laws of Previous Religious Communities (shar’ man qablanā) and the Derivation of Their Rulings - Mohammaed, Sabreen Ali; Makky, Rand Sa’ad (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
This study explores the jurisprudential rule